Effectiveness of Moringa oleifera Leaves for Wound Healing: Systematic review - Anggeria, Elis; Ginting, Chrismis Novalinda; Nababan, Tiarnida (Universitas Prima Indonesia, 2024)
Moringa leaves are a rich source of protein, minerals and fiber. This extract has the potential to be used as an antioxidant, anticancer, anti-inflammatory, antidiabetic and antimicrobial. This systematic review was designed to effectiveness of Moringa Oleifera Leaves for wound healing. Databases were searched for relevant studies: ProQuest, ScienceDirect, Pubmed, Springer Link, and EBSCO to study screening tools used to identify effectiveness of Moringa Oleifera Leaves for wound healing that were published within 2018-2023. Information about study objectives, method, population characteristics, statistical techniques, main findings, and region. Research data analysis was assessed using the ANOVA statistical test. Data from identified studies were analyzed based on objectives, study design, and outcomes. Records identified from: databases (n = 1,375), screened records (n = 1,344), reports searched for retrieval (n = 25), reports assessed for eligibility (n = 17), studies included in the review (n = 9) full text articles in the systematic review. Eligibility of the 9 articles was based on key findings that had been carefully selected to meet the study inclusion criteria. Research with a systematic review of the effectiveness of Moringa leaves for wound healing is very important to provide additional information for patients with acute and chronic wounds who are treated at home or in hospital.